(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Symbolism is a piece of Sport Psychology Skill, where it impact to competitors to achievement in their competition or game. Imagery have better in connection between symbolism capacity and game execution. Game symbolism can be characterized as utilizing all sense to reproduce or make a game involvement in the psyche with the objective of upgrading sport execution amid preparing and rivalry.